Metagenomic analysis of rumen microbial population in dairy heifers fed a high grain diet supplemented with dicarboxylic acids or polyphenols. Issue 1 (December 2016) - De Nardi, Roberta; Marchesini, Giorgio; Li, Shucong; Khafipour, Ehsan; Plaizier, Kees; Gianesella, Matteo; Ricci, Rebecca; Andrighetto, Igino; Segato, Severino
Abstract Background The aim of this study was to investigate the effects of two feed supplements on rumen bacterial communities of heifers fed a high grain diet. Six Holstein-Friesian heifers received one of the following dietary treatments according to a Latin square design: no supplement (control, C), 60 g/day of fumarate-malate (organic acid, O) and 100 g/day of polyphenol-essential oil (P). Rumen fluid was analyzed to assess the microbial population using Illumina sequencing and quantitative real time PCR. Results The P treatment had the highest number of observed species (P  < 0.10), Chao1 index (P  < 0.05), abundance based coverage estimated (ACE) (P  < 0.05), and Fisher's alpha diversity (P  < 0.10). The O treatment had intermediate values between C and P treatments with the exception of the Chao1 index. The PCoA with unweighted Unifrac distance showed a separation among dietary treatments (P  = 0.09), above all between the C and P (P  = 0.05). The O and P treatments showed a significant increase of the familyChristenenellaceae and a decline ofPrevotella brevis compared to C. Additionally, the P treatment enhanced the abundance of many taxa belonging toBacteroidetes, Firmicutes andTenericutes phyla due to a potential antimicrobial activity of flavonoids that increased competition among bacteria. Conclusions Organic acid and polyphenols significantly modified rumen bacterial populations during high-grain feeding in dairy heifers. In particular the polyphenol treatment increased the richness and diversity of rumen microbiota, which are usually high in conditions of physiological rumen pH and rumen function.